Research-based communities of practice in UK higher education - Ng, Lai Ling (Taylor and Francis Online, 2013)
Research is an integral element of the work of higher education institutions, underpinning not only academics’ responsibilities in developing intellectual skills and personal reputations, but contributing to the status of an organisation. Whilst formalised approaches are adopted for developing research, there is a growing trend towards informal groupings or communities of practice. This research, based on interviews with members of five research-based communities of practice, examines the values and motivation of individuals involved in developing research within these higher education communities. The findings reveal that 20 such values are apparent with 12 of these observed in past research; the other eight have emerged from this research and centre on a number of issues, including the need to overcome intellectual isolation, generation of tangible research outcomes, increased synergy and leverage, and creation of collaborative research.